Arterial Blood Supply of Liver Segment IV and Its Possible Surgical Consequences. Issue 4 (19th December 2016) - Alghamdi, T.; Viebahn, C.; Justinger, C.; Lorf, T.
Abstract : The risk of ischemia of segment IV after split liver resection is high. This anatomical study was done to identify the arterial blood supply and the intrahepatic distribution of liver segment IV. The anatomy of segment IV was studied in 29 livers from adult cadavers. To identify the arterial blood supply of segment IV, water and ink were injected into the various branches of the hepatic artery and the outflow through segment IV and discoloration of the liver parenchyma were observed. In 23 of the 29 livers (79.3%), the arterial perfusion of segment IV was separated by a line drawn from the left side of the inferior vena cava at the top of and lateral to the falciform ligament to the medial point of the gallbladder bed. The area lateral to this line was supplied mainly by the right hepatic artery, and the area medial to it was supplied mainly by the left hepatic artery. In addition to the classification system of Couinaud, we describe here a new division of liver segment IV based on arterial blood supply. These anatomical findings may be useful in defining the resection line for split liver to prevent necrosis of segment IV. Abstract : This anatomical study describes in detail the arterial blood supply of segment IV arising from the right hepatic artery and left hepatic artery with a demarcation line in between, and discusses possible surgical consequences.